Legal Protection of Creditors in Financing Agreements through Digital Credit Services (Paylater) - Rahmadi Indra Tektona (Jurnal Hukum Islam, 2021)
This paper discusses the characteristics of financing agreements in digital credit services (paylater) and their legal protection for creditors. The research method uses a doctrinal with legislation  and conceptual approach. Sources of legal materials include primary and secondary legal materials. The analysis uses prescriptive logic and legal reasoning. The results show that the development of electronic-based payment systems has an effect on the creation of electronic money in a payment system that provides convenience, flexibility, and efficiency in transactions. Electronic-based transactions are growing rapidly along with the changing patterns of people's shopping from offline to online. Marketplace in its development creates financial technology, namely paylater. The paylater implementation is carried out with an online agreement contained in an electronic document using a computer network that is connected. Lenders and lenders are linked by the peer to peer lending (P2P) financial services. The characteristics of the financing agreement in the practice of digital credit services (paylater) are the same as conventional agreements which must meet the terms and elements of the agreement as stipulated in the Civil Code. However, in the paylater financing agreement, apart from the borrower and lender, parties are providing financial services to bring together lenders and loan recipients to enter into a lending and borrowing agreement, namely the marketplace, which is outlined in an electronic document. Legal protection for creditors in case of default can apply for dispute resolution through BPSK, Alternative Dispute Resolution Institutions, and District Courts.